2015
DOI: 10.18433/j33w4c
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Activities¬ of 3’-Hydroxypterostilbene: Cytotoxic, Anti-Oxidant, Anti-Adipogenic, Anti-Inflammatory, Histone Deacetylase and Sirtuin 1 Inhibitory Activity

Abstract: -Purpose: Delineate the selected pharmacodynamics of a naturally occurring stilbene 3'-Hydroxypterostilbene. Objective: Characterize for the first time the pharmacodynamics bioactivity in several in-vitro assays with relevant roles in heart disease, inflammation, cancer, and diabetes etiology and pathophysiology. Methods: 3'-Hydroxypterostilbene was studied in in-vitro assays to identify possible bioactivity. Results: 3'-Hydroxypterostilbene demonstrated anti-oxidant, anti-inflammatory, cytotoxic, antiadipogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Collectively, the increased anti-oxidant, anti-adipogenic activity, cell selectivity and COX-2 specificity of 3'-HPT was found in support of its activity in preventing cardiovascular and pulmonary diseases. Coupled with HDAC and SIRT1 inhibitory activity, 3'-HPT has been found to demonstrate protective effects from neurodegenerative diseases and select cancers [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the increased anti-oxidant, anti-adipogenic activity, cell selectivity and COX-2 specificity of 3'-HPT was found in support of its activity in preventing cardiovascular and pulmonary diseases. Coupled with HDAC and SIRT1 inhibitory activity, 3'-HPT has been found to demonstrate protective effects from neurodegenerative diseases and select cancers [14]. …”
Section: Discussionmentioning
confidence: 99%
“…3′-Hydroxypterostilbene ( trans -3,5-dimethoxy-3′,4′-dihydroxystilbene), one of metabolites of pterostilbene [ 30 ], can also be isolated from whole plant of the herb Sphaerophysa salsula , a shrub widely distributed in central Asia and northwest China [ 31 ]. A recent study indicated that 3′-hydroxypterostilbene possesses anti-adipogenic, -inflammatory, -oxidant, and Sirt-1 inhibitory activities [ 79 ]. However, there is a paucity of published studies involving biological activities of 3′-hydroxypterostilbene ( Table 3 ).…”
Section: 3′-hydroxypterostilbenementioning
confidence: 99%
“…It was suggested that methoxylation on hydroxyl groups of pterostilbene or TMS could hinder their metabolism and appeared to have better pharmacokinetic characteristics than their natural occurring analog, resveratrol [ 83 ]. Moreover, Chiou et al [ 79 ] demonstrated that pterostilbene was more potent than resveratrol in preventing colon tumorigenesis via activation of the Nrf2-mediated antioxidant signaling pathway. Likewise, other research group indicated that pterostilbene was more effective than resveratrol as an anti-inflammatory agent for inhibition of colon carcinogenesis in HT-29 human adenocarcinoma cell line [ 19 ].…”
Section: Bioavailability Of Resveratrol and Pterostilbenementioning
confidence: 99%
“…Resveratrol (3,4′,5- trans -trihydroxylstilbene) and pterostilbene (3,5- trans -dimethoxy-4-hydroxystilbene) are two well-known stilbenes which are extensively studied because of their biological properties and potential in therapeutic and preventive application. , Pterostilbene is the dimethyl ether analogue of resveratrol and appears to have greater bioavailability than resveratrol because of its lipophilic nature with two methoxy groups. A novel natural pterostilbene analogue, 3′-hydroxypterostilbene ( trans -3,5-dimethoxy-3′,4′-hydroxystilbene), has been isolated from Chinese folk medicine in Sphaerophysa salsula, Pterocarpus marsupium, and honey bee propolis (Figure ). An in vitro study has documented the pharmacologic activities of 3′-hydroxypterostilbene as having antioxidant, anti-inflammatory, cytotoxic, and antiadipogenic effects . 3′-Hydroxypterostilbene is also reported to be more active than pterostilbene in inducing apoptosis in sensitive and resistant leukemia cells .…”
Section: Introductionmentioning
confidence: 99%